Equitable distribution of CDM projects among developing countries - Alan Silayan (Hamburg Institute of International Economics (HWWA), 2005)
The Clean Development Mechanism as a global flexible mechanism of the Kyoto protocol has a sound basis in theory which has led to its inclusion in the international climate regime. Current trends of the CDM show a clustering of projects towards a few larger developing countries. Contrary to the inclusion of more developing nations in the climate change process, present participation requirements of the CDM have unfortunately prevented 67% of developing nations from engaging in CDM projects. Distinct conditions among developing countries have led to different implementation circumstances. This, in turn, has triggered differences in the capacity to implement CDM projects. Moreover, project investors, in pursuit of an optimum investment portfolio, have had a tendency to support the same cluster of countries. Revisiting the fundamentals of the UNFCCC, criteria can be formulated and applied to all developing countries to identify nations that should be given project priorities in the CDM. Enforcing redistribution of CDM projects among developing nations need not take a complete re-thinking of the CDM concept. An equitable distribution of CDM projects is possible within the current structure of the CDM framework.
Keywords: 330